Transformational Leadership and Work Flexibility Effects on Government Employee Performance with Team Cohesiveness - Moh. Nuh Hudawi; Slamet Ahmadi (Penerbit Goodwood, 2026)
Purpose: This study examines the effect of transformational leadership and work flexibility on government employee performance, with team cohesiveness as an intervening variable. Methodology: The research was conducted among 234 employees of the Directorate General of Surveillance for Marine and Fisheries Resources in Indonesia. A quantitative approach was employed using SEM-PLS, with data collected through questionnaires using a simple random sampling method. Results: The findings show that transformational leadership does not have a significant direct effect on employee performance, whereas work flexibility has a positive effect. However, both transformational leadership and work flexibility significantly influenced team cohesiveness. In addition, team cohesiveness positively affects employee performance and mediates the relationship between transformational leadership and performance and between work flexibility and performance. Conclusions: This study emphasizes the importance of team cohesiveness in enhancing employee performance in the public sector. Leadership practices and flexible work arrangements are more effective when supported by cohesive team environments. Limitations: This study is limited to the employees of Direktorat Jenderal Pengawasan Sumber Daya Kelautan dan Perikanan (Ditjen PSDKP), which may restrict the generalizability of the findings to other organizational contexts. Contributions: This study provides empirical evidence of the mediating role of team cohesiveness and offers practical implications for policymakers and leaders to enhance performance and employee well-being through transformational leadership and flexible work arrangements.